2013
DOI: 10.1128/jb.00485-13
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Haloferax volcanii of 3-Hydroxy-3-Methylglutaryl Coenzyme A Synthase Facilitates Isolation and Characterization of the Active Form of a Key Enzyme Required for Polyisoprenoid Cell Membrane Biosynthesis in Halophilic Archaea

Abstract: Enzymes of the isoprenoid biosynthetic pathway in halophilic archaea remain poorly characterized, and parts of the pathway remain cryptic. This situation may be explained, in part, by the difficulty of expressing active, functional recombinant forms of these enzymes. The use of newly available expression plasmids and hosts has allowed the expression and isolation of catalytically active Haloferax volcanii 3-hydroxy-3-methylglutaryl coenzyme A (CoA) synthase (EC 2.3.310). This accomplishment has permitted studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…Despite our findings here, it has been previously been shown that the yeast HMG-CoA synthase (Erg13p) has higher catalytic efficiency than E. faecalis enzyme (EfmvaS) (Middleton, 1972;Skaff et al, 2012;Vannice et al, 2013). This suggests that the improved catalytic efficiency is not able to overcome the penalty conferred by decreased transcriptional efficiency.…”
Section: Increasing Trans-nerolidol Production By Enhancing the Mva Pcontrasting
confidence: 97%
“…Despite our findings here, it has been previously been shown that the yeast HMG-CoA synthase (Erg13p) has higher catalytic efficiency than E. faecalis enzyme (EfmvaS) (Middleton, 1972;Skaff et al, 2012;Vannice et al, 2013). This suggests that the improved catalytic efficiency is not able to overcome the penalty conferred by decreased transcriptional efficiency.…”
Section: Increasing Trans-nerolidol Production By Enhancing the Mva Pcontrasting
confidence: 97%
“…Moreover, Hfx. volcanii HMG-CoA reductase is the first such enzyme that is not sensitive to feedback inhibition by its substrate, acetoacetyl-CoA [68]. Likewise, known feedback inhibitors of mevalonate-5-kinases do not inhibit the Methanosarcina mazei enzyme, making it the sole member of a third class of mevalonate kinases defined on the basis of inhibition profile [69].…”
Section: Phosphodolichol Biosynthesis In Archaeamentioning
confidence: 99%
“…The PCR products and pTA963 were restriction digested using EcoRI and BamHI, ligated using T4 DNA ligase, transformed into H. volcanii H1209 cells, and stored in 20% glycerol at Ϫ80°C as previously described (8). The pTA963 vector contains a tryptophan-inducible promoter and an N-terminal His affinity tag directly upstream of the EcoRI and BamHI subcloning site.…”
Section: Methodsmentioning
confidence: 99%
“…Recovery of active enzyme allowed confirmation of the proposed function (8) and suggested that this approach could be extended to investigate the functions of proteins that had ambiguous annotations. Recovery of active enzymes has now led to the identification of H. volcanii IPK (HvIPK) and the monophosphate-specific phosphomevalonate decarboxylase (PMD) and, thus, the first experimental demonstration of both of these remaining reactions of the alternate MVA pathway in an archaeon.…”
mentioning
confidence: 99%